1996
DOI: 10.1007/bf03172938
|View full text |Cite
|
Sign up to set email alerts
|

Bullies and victims in schools in central and southern Italy

Abstract: Anonymous questionnaires assessing the amount and nature of bullying/victimization were given to 1379 primary and middle school pupils (8-11; 11-14yrs) in two towns of Central and Southern Italy, Florence and Cosenza. The questionnaire closely followed the design of Olweus (1991) and Whitney and Smith (1993). Results were analysed in terms of percentages of bullying others and being bullied, types of bullying behaviour, where it occurred and who were the perpretators. Bullying )vas reported in both Italian a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
73
2
6

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 9 publications
13
73
2
6
Order By: Relevance
“…This proportion is extremely high, but it is not possible to compare it with other findings because no other studies have taken into account jointly all these kinds of victimization. However, with regard to being bullied at school, prevalence rates are consistent with another independent Italian study (Genta et al, 1996), and those reported internationally (Smith et al, 1999). Inter-parental violence was reported by one in three children, as well as direct parental abuse (over one-third), which is also in line with findings from Straus (1979).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This proportion is extremely high, but it is not possible to compare it with other findings because no other studies have taken into account jointly all these kinds of victimization. However, with regard to being bullied at school, prevalence rates are consistent with another independent Italian study (Genta et al, 1996), and those reported internationally (Smith et al, 1999). Inter-parental violence was reported by one in three children, as well as direct parental abuse (over one-third), which is also in line with findings from Straus (1979).…”
Section: Discussionsupporting
confidence: 89%
“…To measure prevalence of direct and indirect bullying and victimization, the Italian modified version (Genta et al, 1996) of the Olweus bullying questionnaire (Olweus, 1993) was used. Measurement of 'direct bullying' was based on how often the students had called others by nasty names, physically hurt them, taken their belongings or threatened them in the previous three months (four items).…”
Section: Bullying and Victimizationmentioning
confidence: 99%
“…Cowie et al [1994] have shown that cooperative group work reduces the extent of victimisation of vulnerable children, even in difficult conditions. Because there is strong evidence that victims are most often bullied by someone from their own class [Genta et al, 1996;O'Moore et al, 1997a;Whitney and Smith, 1993], methods of teaching and discipline that draw on positive methods are likely to achieve more positive attitudes and behaviour in pupils. Foster and Thompson [1991] present a striking example of the benefits of developing a nonviolent sanctions policy in school.…”
Section: Preventive Strategiesmentioning
confidence: 98%
“…To measure the frequency of school bullying, we adopted the classical, widely used bully victim questionnaire, originally proposed by Olweus (1986Olweus ( , 1996, modified by Whitney and Smith (1993) and adapted for Italy by Genta, Menesini, Fonzi, Costabile, and Smith (1996).…”
Section: School Bullyingmentioning
confidence: 99%